Penilaian Tingkat Keberlanjutan Objek Wisata Kawasan Pesisir di Kota Makassar - Ratih Puspitasari; Mukti Ali; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The coastal area of ​​Makassar City has several coastal tourism potentials that can be developed in the form of a stretch of beach at the sea such as Akkarena Beach. But in its development, various kinds of problems arise relating to economic, social and environmental. This certainly affects the level of sustainability of the tourist objects of the Makassar City coastal area. This study aims to determine the level of sustainability and sensitive variables (attributes) that affect the level of sustainability of coastal tourism objects in Makassar City. The analytical method used is a qualitative and quantitative descriptive method that is supported by the application of rapfish in the Multidimensional Scaling (MDS) and leverage models. The results show that overall the Akkarena Beach has a fairly sustainable category. Where the economic dimension is categorized quite sustainable with tourism development and promotion attributes being the most sensitive attributes, the social dimension is sustainable with level of crime as sensitive attributes and environmental dimension has a sustainable category with land use deviations as sensitive attributes.